Consolidating a MAPE-K-Based Architecture for Dynamic Difficulty Adjustment: A Bottom-Up Approach - Souza, Carlos Henrique R.; Berretta, Luciana de O.; Carvalho, Sérgio T. de (Anais do Workshop sobre Engenharia de Software para Desenvolvimento de Jogos (SE4Games); 2025: Anais do I Workshop sobre Engenharia de Software para Desenvolvimento de JogosDO - 10.5753/se4games.2025.14865, 2025)
Game developers are increasingly adopting Dynamic Difficulty Adjustment (DDA) mechanisms to tailor gameplay experiences for individual players. However, existing solutions often lack modularity and generalization, limiting their applicability across diverse games, genres, and mechanics. This paper presents the consolidation of a modular DDA architecture based on the MAPE-K loop, designed to support hybrid adaptation strategies. The architecture was developed incrementally by integrating previously evaluated components, including both rule-based and AI-driven mechanisms. While earlier studies validated these components in isolation, we now unify them into a single, cohesive architectural solution.